Migrants and terrorism: A link or misconception - ELENA TILOVSKA-KECHEDJI (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: The research paper’s overarching goal is to dispel the widespread belief that "every immigrant is a terrorist" by showing that the vast majority of terrorists are actually citizens of the countries where they commit their atrocities.Method: Documentary research was used extensively from 2013 to 2016 to mine secondary sources for relevant information.Findings: The paper concludes by discussing the new trend toward the securitization of migration and its analysis of the connection between terrorism and migration. Based on the findings, it appears that after September 11th, migration shifted from being an economic phenomenon to one related to security and that politicians and the media painted a negative picture as a result. We cannot rule out the possibility that migration is connected to terrorism, perhaps not directly as depicted in the media but rather through a deliberate process led by terrorist organizations, even though much has changed since the earliest days of migration.Implications/Novel Contribution: The empirical impact on real life and how migrants will be perceived in real life is the practical significance of this paper. Terrorist attacks have increased in frequency and concern throughout the West, but there is a lack of literature addressing this topic.